How clinical practitioners assess frailty in their daily practice: an international survey - Bruyère, Olivier; Bauer, Jürgen M. (Aging clinical and experimental research, 2017)
IntroductionVarious operational definitions have been proposed to assess the frailty condition among older individuals. Our objective was to assess how practitioners measure the geriatric syndrome of frailty in their daily routine.MethodsAn online survey was sent to national geriatric societies affiliated to the European Union Geriatric Medicine Society (EUGMS) and to members of the European Society for Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (ESCEO).ResultsA total of 388 clinicians from 44 countries answered to the survey. Most of them were medical doctors (93%), and their primary field of practice was geriatrics (83%). Two hundred and five clinicians (52.8%) always assessed frailty in their daily practice, 38.1% reported to “sometimes” measure it, and 9.1% never assess it. A substantial proportion of clinicians (64.9%) diagnose frailty using more than one instrument. The most widely used tool was the gait speed test, adopted by 43.8% of the clinicians, followed by clinical frailty scale (34.3%), the SPPB test (30.2%), the frailty phenotype (26.8%) and the frailty index (16.8%).ConclusionA variety of tools is used to assess frailty of older patients in clinical practice highlighting the need for standardisation and guidelines.